Biliary Tract Abnormalities as a Cause of Distal Bowel Gas in Neonatal Duodenal Atresia - Surasak Puvabanditsin; Marissa Botwinick; Charlotte Wang Chen; Aditya Joshi; Rajeev Mehta (Case Reports in Surgery)
Background. The presence of distal bowel gas in an infant does not exclude the diagnosis of duodenal atresia. Case Presentation. We report a term neonate with Down syndrome. The infant developed vomiting and cyanosis with each feeding soon after birth. Plain film abdominal X-rays showed a nonspecific gas-filled stomach and small bowel. Duodenal atresia and an anomalous common bile were noted on an upper GI study and exploratory laparotomy. Conclusion. In the absence of a “double bubble” appearance and intestinal gas distally on a plain radiograph, one must not exclude duodenal atresia as the differential diagnosis.